2016
DOI: 10.1249/mss.0000000000000876
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ACL Reconstruction in Patients with Diabetes

Abstract: Purpose Diabetes has been associated with adverse outcomes following various types of surgery. There is no previously published data regarding the impact of diabetes on outcomes from anterior cruciate ligament (ACL) reconstruction (ACLR). The purpose of this study was to test the hypotheses that diabetes is associated with worse clinical outcomes and a higher prevalence of subsequent surgeries following ACLR. Methods ACL deficient patients (n=2198) undergoing unilateral ACLR from a multicenter prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Finally, the remaining demographics and comorbidities failed to show any association with contralateral ACLR, including obesity or morbid obesity, type 1 or type 2 diabetes, and a history of anxiety. This is in agreement with other studies that have also shown no significant association between these factors and graft failure or contralateral ACLR [3, 6]. Some authors have suggested that patients with an elevated BMI and diabetes may be less active after ACLR and therefore at reduced risk of contralateral injury [6].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the remaining demographics and comorbidities failed to show any association with contralateral ACLR, including obesity or morbid obesity, type 1 or type 2 diabetes, and a history of anxiety. This is in agreement with other studies that have also shown no significant association between these factors and graft failure or contralateral ACLR [3, 6]. Some authors have suggested that patients with an elevated BMI and diabetes may be less active after ACLR and therefore at reduced risk of contralateral injury [6].…”
Section: Discussionsupporting
confidence: 91%
“…Anterior cruciate ligament reconstruction (ACLR) is one of the most commonly performed orthopaedic procedures [14, 22]. Both short‐ and long‐term clinical outcomes after ACLR have been well characterized [3, 7, 11, 15, 17, 23, 24, 27, 30, 31]. Perioperative complications occur infrequently, with the rate of symptomatic thromboembolic events reported at between 0.53 and 4.0% [11, 15, 30], septic arthritis between 0.14 and 0.48% [17, 23, 31], urinary tract infection at 0.74% [27], and an inpatient mortality rate under 0.01–0.02% [11, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Acutely elevated blood glucose may directly promote thrombosis and microvascular injury and is associated with a blunted cell-mediated immunity response to pathogens via impaired leukocyte mobilization, chemotaxis, and phagocytosis. 2,28 In addition, DM is independently associated with impaired promotion of a proinflammatory state in response to pathogens, regardless of HbA1c levels. 28 In patients who underwent knee arthroscopy, Canciene et al 8 found that uncontrolled DM was associated with an increased risk of postoperative infection in a national database study similar to that of Basques et al 7 An analysis of the Multicenter Orthopaedic Outcomes Network (MOON) database for patients undergoing anterior cruciate ligament reconstruction (ACLR) including 2,198 patients with a 6-year follow-up demonstrated that DM was a notable risk factor for surgical site infection (OR = 18.8).…”
Section: Infectionmentioning
confidence: 99%
“…2,28 In addition, DM is independently associated with impaired promotion of a proinflammatory state in response to pathogens, regardless of HbA1c levels. 28 In patients who underwent knee arthroscopy, Canciene et al 8 found that uncontrolled DM was associated with an increased risk of postoperative infection in a national database study similar to that of Basques et al 7 An analysis of the Multicenter Orthopaedic Outcomes Network (MOON) database for patients undergoing anterior cruciate ligament reconstruction (ACLR) including 2,198 patients with a 6-year follow-up demonstrated that DM was a notable risk factor for surgical site infection (OR = 18.8). 9 A separate study analyzed a cohort of patients who underwent revision ACLR from both the MOON database and the Multicenter ACL Revision Study (MARS), with a 2-year follow up.…”
Section: Infectionmentioning
confidence: 99%